Decisions of the Young Generation in Using Digital Banking Services: Structural Equation Modeling Analysis - Anggari Kresnowati (Bulletin of Islamic Economics, 2022)
This study aims to create a new research model with a variety of variables to comprehend and forecast the key factors that influence young people's decisions to use digital banking. This study uses a quantitative method with a multivariate analysis approach, for this reason, the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis technique is used. According to the findings of this study, respondents' perceptions of the quality of digital banking products such as mobile banking, SMS banking, phone banking, and internet banking do not influence them to continue using digital banking. Considerations of usability, benefits, risks, and ease of use dominated respondents' decisions to use digital banking services.